2005
DOI: 10.5210/fm.v10i8.1263
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion pattern of Linux: An assessment on major technology dimensions

Abstract: This paper attempts to gain an understanding of the diffusion dynamics of Linux by assessing it on Rogers' technology dimensions -relative advantage, compatibility, complexity, observability, and trialability. The analysis makes clear that Linux possesses greater relative advantage than its proprietary competitors because of its low cost, lower susceptibility to bugs and crashes, resilience to obsolescence, ability to run on older machines and higher perceived security. Linux is facing compatibility problems w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…OSS offers two advantages over proprietary software concerning trialability: it can be freely downloaded from the Internet without prior registration with a vendor, and there are no limitations in time or functionality when using the software. Because of these properties, some authors have argued that OSS possesses -unlimited trialability‖ [Kshetri, 2005]. Previous studies have shown that organizations generally agree that OSSS has a high degree of trialability [Dedrick and West, 2003;Ven and Verelst, in press].…”
Section: Hypothesis 1 Organizations That Perceive Osss To Be Reliablmentioning
confidence: 99%
“…OSS offers two advantages over proprietary software concerning trialability: it can be freely downloaded from the Internet without prior registration with a vendor, and there are no limitations in time or functionality when using the software. Because of these properties, some authors have argued that OSS possesses -unlimited trialability‖ [Kshetri, 2005]. Previous studies have shown that organizations generally agree that OSSS has a high degree of trialability [Dedrick and West, 2003;Ven and Verelst, in press].…”
Section: Hypothesis 1 Organizations That Perceive Osss To Be Reliablmentioning
confidence: 99%